Introducing abstraction, diversity, and speech dynamics. Issue 1 (12th July 2019) - Harrington, Jonathan; Pouplier, Marianne; Reinisch, Eva
Abstract : The editorial provides an overview of the main themes that are covered by the seven papers that form part of the special collection.